2023
DOI: 10.1177/00469580221146827
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Dilemmas, Challenges, and Opportunities of Adolescent Fatherhood: An Exploratory Case Study

Eugene Musiiwa Makhavhu,
Tendani Sara Ramukumba,
Mmajapi Elizabeth Masala-Chokwe

Abstract: Teenage pregnancy is a significant concern for society, and the effect on education is immense. In South Africa, policies were thus introduced allowing pregnant school-going children to continue attending class until the baby’s birth. However, research on adolescent pregnancy generally ignores teenage fathers and focuses mostly on teenage mothers. Parents of teenage girls are also encouraged to offer support to their children, but the same cannot be said about adolescent fathers. They confront numerous barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…On the contrary, studies reported fathers wanting to be present and involved during their child’s birth and infancy, but being prevented from doing so. This was mentioned in studies looking at adolescent fathers who wished to build a relationship with their child as well as provide financial support [ 35 , 36 , 39 ]. For many adolescent fathers, having a child limited their education as generating income became a higher priority.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the contrary, studies reported fathers wanting to be present and involved during their child’s birth and infancy, but being prevented from doing so. This was mentioned in studies looking at adolescent fathers who wished to build a relationship with their child as well as provide financial support [ 35 , 36 , 39 ]. For many adolescent fathers, having a child limited their education as generating income became a higher priority.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies presented data reflecting both traditional and more egalitarian views coming from different sample cross-sections. Some studies inferred influential factors, concluding that fathers with higher levels of education, who lived in more urban areas, had more knowledge about maternity services, and/or were from younger age cohorts were more likely to be involved partners [ 21–23 , 26 , 29 , 35 , 36 , 39–41 , 47 , 49 ]. Men from these groups more than others expressed the desire to be active participants in the pregnancy and childbirth process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations